Serum Levels of IL-33 and Correlation with IL-4, IL-17A, and Hypergammaglobulinemia in Patients with Autoimmune Hepatitis. (24th June 2018) - Liang, Ma; Liwen, Zhang; Yun, Zhuang; Yanbo, Ding; Jianping, Chen
Abstract : This study investigated the role of IL-33 in the pathogenesis of autoimmune hepatitis (AIH). The levels of IL-33/sST2 and Th1/Th2/Th17-type cytokines were determined by enzyme-linked immunosorbent assay in serum samples obtained from 30 AIH patients and 20 healthy controls (HCs). In addition, a murine model of experimental AIH (EAIH) was established to investigate the role of IL-33 in disease progression. The serum levels of IL-33, sST2, Th17 cytokines (IL-17A), Th1 cytokines (IFN- γ, TNF- α ), and Th2 cytokines (IL-4) were significantly elevated in AIH patients compared to HCs. Following immunosuppression therapy, serum levels of IL-33 and sST2 were significantly decreased. Additionally, the serum levels of IL-33 in AIH patients were correlated positively with markers of hypergammaglobulinemia (IgG, IgM, and IgA) and liver injury ( γ -GT/ALP). Also, the serum levels of IL-33 in AIH patients were correlated positively with proinflammatory cytokine levels (IL-17A and IL-4). Interestingly, treatment of EAIH mice with a specific IL-33 neutralizing antibody significantly reversed the increasing trend in serum ALT/AST and inhibited the production of the type 2 (IL-4) and type 17 cytokines (IL-17) but not the type 1 cytokine (IFN- γ ). Our findings highlight the possible role of the IL-33/sST2 axis in the progression of AIH, opening a new door for developing a novel therapeutic strategy for AIH.